Modern Aspects of Home Economics Education and Slovenia - Martina Erjavšek (Center for Educational Policy Studies Journal)
Home economics operates in the academic, curriculum and social realms, as well as in everyday life. Due to its multidisciplinarity, it includes and interconnects the contents of different disciplines (e.g., healthy lifestyle, nutrition, dietetics, textiles, home, family, consumption, personal and family economics, design and technology), which are considered in terms of meeting the needs of the individual, family, and society. Home economics education and literacy play an important role in acquiring knowledge and skills that help raise the quality of life of the individual, family, and society. With the development of society, the needs of both the individual and the family are changing; therefore, changes are also needed in home economics education, which is reflected in the updating of the subject curricula. The goals and contents in the curriculum must reflect and meet the needs of the current society and take into account the cultural dependence and social determinism of the home economics field. To a certain extent, the current curriculum of the subject home economics in Slovene elementary schools already includes some content areas that have been recognised as important for meeting the needs of society. These relate to healthy lifestyle, nutrition, health, textiles, consumption, economics, family, environment and sustainable development. Given the perceived needs of society, the use of household appliances, home contents, and first aid should be additionally included in home economics education in Slovenia, and students should be encouraged to develop social and communication skills. It is also necessary to consider the appropriate placement of the subject in the curriculum, as it is necessary to implement home economics education in the entire elementary school education. Doing so will enable the acquisition of knowledge and skills needed in society and, therefore, the appropriate level of home economics literacy of the individual.